PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X IPS DI SMA NEGERI 1 CERENTI KAB. KUANTAN SINGINGI - Nur, Fauzan; Suarman, Suarman; Hendripides, Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this research is to know the effect learning motivation to students learning result in SMAN 1 Cerenti. The population of this research is all students of grade X IPS in SMAN 1 Cerenti which is consist of 138 students and this research use proportional sample technique, it is taking sample from some sub population with the proportional quantity. To measure the quantity of population using issac table with error degree 10%. Based on Issac table with error degree 10%, if population in this research is 138, so the sample is 92 students. Data is collected by using quisioner about learning motivation which is given to respondent. Data analysis uses simple linear regresi test. Based on the result of learning motivation effect of X IPS students in Economic subject in SMAN 1 Cerenti is 0,100 or 10%, meanwhile the rest is 90% effected by other factor that is not researched in this research such as intergency factor, attention, interest talent, ripeness, and readiness. For teacher, it is supposed to give praise, gift, and make new and creative learning method that is more interesting, so that it can increase learning motivation and trigger student achievement.Key Words : Learning motivation, learning outcomes.